1975
DOI: 10.1099/00207713-25-4-329
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of the Relationship Between Mycobacterium, Rhodochrous Group, and Nocardia by Use of Hypothetical Median Organisms

Abstract: A total of 1,054 strains was allocated to species of the genera Mycobacterium, Nocardia, and Gordona (the rhodochrous group) on the basis of 88 characters, and hypothetical median organisms (HMOs) were derived for each species. Numerical analysis was carried out, treating these HMOs as operational taxonomic units. The dendrogram obtained showed that strains received as members of the rhodochrous group, including "Mycobacterium" rhodochrous, and strains named previously by the present author as Gordona, constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 13 publications
(10 reference statements)
1
9
0
Order By: Relevance
“…As shown previously by Tsukamura (14,17,21) and in the present study, slowly growing and rapidly growing mycobacteria seem to be valid taxa of generic (or subgeneric) rank. Strains of a few species of rapidly growing mycobacteria remained as outsiders, namely, those of M. agri, M. smegnzatis, and M. vaccae, as did strains of scotochromogenic, rapidly growing mycobacteria isolated from a bovine thelitis lesion by Shimizu et al (11).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…As shown previously by Tsukamura (14,17,21) and in the present study, slowly growing and rapidly growing mycobacteria seem to be valid taxa of generic (or subgeneric) rank. Strains of a few species of rapidly growing mycobacteria remained as outsiders, namely, those of M. agri, M. smegnzatis, and M. vaccae, as did strains of scotochromogenic, rapidly growing mycobacteria isolated from a bovine thelitis lesion by Shimizu et al (11).…”
Section: Discussionsupporting
confidence: 55%
“…These clusters were composed of: (A) slowly growing mycobacteria; (B) intermediate mycobacteria; (C) rapidly growing mycobacteria; and (D) rhodococci and nocardiae. Previously, Tsukamura (17,21) (thiopene-2-carboxylic acid hydrazide), nitrate reduction, and the 2-week aryhlfatase test. These two subgroups form the TB complex.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few numerical taxonomy studies of rapidly growing, scotochromogenic mycobacteria have been reported (8,22,27,30). In these studies, M. neoaurum was not clearly separated from M. parafortuitum (€9, and "M. tokaiense" was not clearly distinguished from "M. chubuense" (27).…”
Section: Discussionmentioning
confidence: 99%
“…The set of characters shown in Table 2 was used for analysis of the relationship among Mycobacteriurn, Gordona, and Nocardia (23). Only 57 of these characters were effective for differentiation between Nocardia strains (omitting strain 71, which is now identified as Mycobacterium intracellulare).…”
Section: Materlals and Methodsmentioning
confidence: 99%